2007
DOI: 10.1128/aem.00578-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofilm Formation by Pseudoalteromonas spongiae on Induction of Larval Settlement of the Polychaete Hydroides elegans

Abstract: The effects of culture conditions and chloramphenicol treatment on the induction of the marine bacterium Pseudoalteromonas spongiae to larval settlement of Hydroides elegans were investigated. The results showed that P. spongiae cells grown in the medium containing both yeast extract and peptone (YP-grown P. spongiae) was highly inductive to larval settlement, whereas P. spongiae cells grown in the medium containing only peptone (P-grown P. spongiae) or YP-grown P. spongiae cells treated with chloramphenicol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…The formation of biofilm is very important for the adhesion of subsequent fouling organisms. The studies had proved that bacterial biofilm of Pseudoalteromonas spongiae was associated with its induction of larval settlement of the polychaete Hydroides elegans and the settlement was correlated with bacterial density (Lau et al, 2005;Huang et al, 2007), and the reports suggested that the extracellular polymers of benthic diatoms induced larval settlement in the polychaete Hydroides elegans (Lam et al, 2003(Lam et al, , 2005. Similarly, bacterial biofilm promoted the settlement of Ulva spores and Balanus improvisus cyprid (Joint et al, 2002;Tait and Havenhand, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of biofilm is very important for the adhesion of subsequent fouling organisms. The studies had proved that bacterial biofilm of Pseudoalteromonas spongiae was associated with its induction of larval settlement of the polychaete Hydroides elegans and the settlement was correlated with bacterial density (Lau et al, 2005;Huang et al, 2007), and the reports suggested that the extracellular polymers of benthic diatoms induced larval settlement in the polychaete Hydroides elegans (Lam et al, 2003(Lam et al, , 2005. Similarly, bacterial biofilm promoted the settlement of Ulva spores and Balanus improvisus cyprid (Joint et al, 2002;Tait and Havenhand, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a global regulation signals for bacterial activities, AHLs may affect not only the biofilm composition, but also the consequence of biofilm activities in environment such as biofouling development, nitrogen fixation, sulfate reduction, the degradation of organic matter and, moreover, provide shelter for certain bacteria (Costerton et al, 1995;Qian, 1999;Decho, 2000;Valle et al, 2004;Queck et al, 2006;Huang et al, 2007b;Case et al, 2008). For examples, the cross-domain communication by AHLs between bacteria in biofilms and spores of green alga Ulva indicated a direct function of AHLs in biofouling development (Joint et al, 2002).…”
Section: Dynamics Of Ahl-producing Bacteria During Subtidal Biofilm Fmentioning
confidence: 99%
“…The assemblage of these attached microorganisms on a surface is referred to as a marine biofilm (Cooksey and Wigglesworth-Cooksey, 1995;Costerton et al, 1995). Marine biofilms play important roles in various biological processes, such as the biofouling development, nitrogen fixation, sulfate reduction and so on, therefore are important topics in marine ecological study (Costerton et al, 1995;Qian, 1999;Decho, 2000;Huang et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms were the earliest eukaryotic colonizer during biofouling formation. The attached diatoms played a signifi cant role in the development of the subsequent macrofouling community (Joint et al, 2002;Huang et al, 2007;Qian et al, 2007). Only a few studies have focused on the community of biofi lm diatoms in the marine environment (Molino and Wetherbee, 2008;Sweat and Johnson, 2013).…”
Section: Discussionmentioning
confidence: 99%